Getting started in ballet : a parent's guide to dance education - Paskevska, Anna (Oxford University Press, 1997)
Many children dream of being a ballerina. Chin raised with purpose, arms high above head, they twirl clumsily around the living room and leap tirelessly in the air. Sooner or later they're bound to say, ""I want to dance."" Now what do you do? How do you know if the time is right? Where's the best place to start? In Getting Started in Ballet, Anna Paskevska draws from her training at the Paris Opera Ballet School and the Royal Ballet School in London and her career as a professional dancer and teacher to offer a step-by-step introduction to dance education for parents with children startin